Role of degradative enzyme-producing microbial consortia in agricultural waste composting - Goud, Merugu Shashank; Thakur, Swagata (Indian Farming, 2024)
India is an agriculture-based country and everyday huge amount of agro-wastes are generated. Almost half of the wastes find their fate in burning which creates considerable air pollution and soil degradation. Decomposition of these heterogeneous organic matters into compost will help in a great way to solve the problems. Several fungi and bacteria like Cellulomonas sp., Trichoderma viride, Aspergillus niger, Pleurotus, Trichoderma, Talaromyces, Bacillus, and Chryseobacterium spp. can produce different types and amounts of degradative enzymes which enhances the process of composting. They can be utilized as microbial consortia after isolation from the environment and passing through the proper screening process. The isolated microbes are screened for degradative enzyme production, and then enzyme profile needs to be prepared. The potential microbes should be further characterized and ideal growth parameters should be defined. The microbes then have to be checked for compatibility with each other for making consortia. Composts should be prepared in pits along with microbial consortia and nitrogen-rich organic sources to improve the process. Propermoisture and aeration should be maintained for good quality compost, which is of great importance in organic farming. Composting gives an alternative to environment-friendly waste treatment and thus gives us an opportunity to convert waste to wealth.